Actualizing Blue Economy: Multi-Track Diplomacy in Supporting Indonesia – Philippines Ocean Economy Cooperation (2014-2017) - Yossica Novyanti Lyonitha Putri; Anggara Raharyo (President University, 2019)
This article aims to analyse Indonesia’s diplomacy strategy to the Philippines in actualizing blue economy from 2014 until 2017. Indonesia's geographical condition, which is the largest archipelagic country in the world and is located within the coral triangle region brace Indonesia to have enormous marine potentials and high valuation. Indonesia during the reign of President Joko Widodo committed to develop their economy from the marine sector using blue economic principle– the utilization of marine potential by considering the long-term calculation between social and the environmental sustainability. The authors use complex interdependence theory which shows that cooperation between Indonesia and the Philippines by involving the role of non-governmental organizations and business stakeholders contribute to solve problems and support the successful implementation of the blue economy. Through a qualitative analytic research method, this article finds Indonesia’s diplomacy strategy as the effort to implement blue economy by using Multi-track Diplomacy approach, which focuses on the government (Track I) through the signing of Joint Declaration of Sea Connectivity between the two countries, non-government professional (Track II) through the establishment of the Working Group for Coral Triangle Initiatives involving Non-Governmental Organizations in Indonesia, and business (Track III) through the Coral Triangle Initiatives-Business Forum to the Philippines during the administration of President Joko Widodo in 2014-2017.Artikel ini bertujuan untuk menganalisis strategi diplomasi Indonesia ke Filipina dalam mengaktualisasikan ekonomi biru dari 2014 hingga 2017. Kondisi geografis Indonesia, yang merupakan negara kepulauan terbesar di dunia dan terletak di dalam kawasan segitiga karang menganugerahkan Indonesia dengan potensi laut yang sangat besar dan valuasi tinggi. Indonesia pada masa pemerintahan Presiden Joko Widodo berkomitmen untuk mengembangkan ekonomi mereka dari sektor kelautan menggunakan prinsip ekonomi biru– pemanfaatan potensi kelautan dengan mempertimbangkan perhitungan jangka panjang antara keberlanjutan sosial dan lingkungan. Penulis menggunakan teori ‘complex interdependence’ yang menunjukkan bahwa kerja sama antara Indonesia dan Filipina dengan melibatkan peran organisasi non-pemerintah dan pemangku kepentingan bisnis berkontribusi untuk memecahkan masalah dan mendukung keberhasilan implementasi ekonomi biru.Menggunakan metodologi penelitian kualitatif, skripsi ini menjelaskan strategi diplomasi Indonesia dalam upaya untuk mengaktualisasikan ekonomi bitu dengan menggunakan langkah Multi-track Diplomacy, dengan fokus dalam kerjasama negara (Track I) melalui penandatanganan Joint Declaration of Sea Connectivity antara kedua negara, organisasi non-pemerintah (Track II) melalui penetapan kelompok kerja untuk kerjasama Coral Triangle Initiative dengan melibatkan organisasi non-pemerintah di Indonesia, dan bisnis (Track III) melalui Forum Bisnis Regional Coral Triangle Initiatives kepada Filipina selama masa administrasi Presiden Joko Widodo tahun 2014-2017.